A Retrospective Study of Cytogenetic Results From Amniotic Fluid in 5328 Fetuses With Abnormal Obstetric Sonographic Findings. (19th May 2017) - Zhang, Shuo; Lei, Caixia; Wu, Junping; Sun, Haiyan; Yang, Yuezhou; Zhang, Yueping; Sun, Xiaoxi
Abstract : Objectives: The purpose of this study was to evaluate the diagnostic utility of karyotype analysis of amniotic fluid for fetuses with abnormal sonographic findings and to determine the detection rates of abnormal karyotypes. Methods: We conducted a retrospective study of 5328 fetuses with abnormal sonographic findings in the first or second trimester enrolled from October 1998 and September 2015. Cytogenetic results from amniotic fluid were obtained in all of these pregnancies. Sonographic abnormalities were stratified according to anatomic system involvement. Results: A total of 238 abnormal karyotypes were encountered in the 5328 fetuses (4.5%). The highest rate of chromosomal anomalies was in fetuses with structural abnormalities in multiple organ systems (25.7%), followed by an abnormal amniotic fluid volume (7.9%), structural abnormalities in a single system (7.3%), multiple nonstructural anomalies (7.2%), isolated placental abnormalities (7.1%), and isolated soft markers for aneuploidy (2.4%; P < .01). Among abnormalities in a single system, gastrointestinal and neck/body fluids had particularly high detection rates (26.1% and 26.2%, respectively). A detailed analysis suggested that the probability of an abnormal karyotype among every anatomic system was statistically significant ( P < .01). This study identified several common indications with extremely high abnormal rates: duodenal atresia (53.1%), holoprosencephaly (48.8%), fetal hydrops (39.5%), cerebellar hypoplasia (32.0%), cystic hygroma (31.5%), absent/short nasal bone (11.0%), and bilateral choroid plexus cysts (8.5%). Conclusions: Cytogenetic analysis has important clinical utility in a wide range of settings, such as prenatal diagnosis. For fetuses with indications of a highly abnormal detection rate, karyotype analysis should be suggested.